2013
DOI: 10.5194/acp-13-3149-2013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bark beetle infestations on monoterpene emissions and secondary organic aerosol formation in western North America

Abstract: Over the last decade, extensive beetle outbreaks in western North America have destroyed over 100 000 km2 of forest throughout British Columbia and the western United States. Beetle infestations impact monoterpene emissions through both decreased emissions as trees are killed (mortality effect) and increased emissions in trees under attack (attack effect). We use 14 yr of beetle-induced tree mortality data together with beetle-induced monoterpene emission data in the National Center for Atmospheric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 59 publications
(68 reference statements)
1
54
0
Order By: Relevance
“…This stressor increases OVOC emissions in the short-term, but after prolonged exposure to the stressor, plants close their stomata to conserve water and a resulting drop in OVOC emissions occurs (Filella et al, 2007;Graus et al, 2013). This same threshold effect was not observed for terpene foliar concentrations and terpene emissions from Mediterranean tree species and C4 crops (Blanch et al, 2009;Graus et al, 2013). However, other studies have demonstrated that under severe enough drought stress, monoterpene emissions also begin to decrease (Ormeno et al, 2007;Simpraga et al, 2011).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This stressor increases OVOC emissions in the short-term, but after prolonged exposure to the stressor, plants close their stomata to conserve water and a resulting drop in OVOC emissions occurs (Filella et al, 2007;Graus et al, 2013). This same threshold effect was not observed for terpene foliar concentrations and terpene emissions from Mediterranean tree species and C4 crops (Blanch et al, 2009;Graus et al, 2013). However, other studies have demonstrated that under severe enough drought stress, monoterpene emissions also begin to decrease (Ormeno et al, 2007;Simpraga et al, 2011).…”
Section: Introductionmentioning
confidence: 69%
“…It is well established that herbivory can increase monoterpene, sesquiterpene, and small OVOC emission rates and substantially alter the BVOC profile (Achotegui-Castells et al, 2013;Hu et al, 2008;Laothawornkitkul et al, 2008;Semiz et al, 2012). The presence of herbivore infestation can increase BVOC emissions by 4-to 20-fold (Amin et al, 2012(Amin et al, , 2013Berg et al, 2013), and this response can last for several weeks (Priemé et al, 2000). These results suggest that herbivore stress could have a substantial impact on SOA formation in forest environments in the future.…”
Section: Introductionmentioning
confidence: 87%
“…In some cases, this underestimation has been shown to be due to problems with the underlying emission inventories, particularly for domestic wood burning in wintertime (Simpson et al, 2007;Denier van der Gon et al, 2015). There may also be sources of biogenic secondary organic aerosol (BSOA) arising from previously neglected VOC emissions such as those induced by biotic stress (Berg et al, 2013;Bergström et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tree mortality, for example associated with insect infestation or disease, can modulate biosphere-atmosphere exchange, generating transitory perturbations in air quality (Berg et al, 2013;Geddes et al, 2016). However, conversion of land cover, for example via clearing, can lead to longterm changes in surface properties and therefore atmospheric composition.…”
Section: Introductionmentioning
confidence: 99%